2009
DOI: 10.1103/physrevlett.103.227401
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Cooperative Vibrational Relaxation of the NH-, OH-, and OD-Stretching Modes in Hydrogen-Bonded Liquids Using Infrared Pump-Probe Spectroscopy

Abstract: Evidence for cooperative vibrational relaxation of the NH-, OH-, and OD-stretching modes in hydrogen-bonded liquids using infrared pump-probe spectroscopy Shaw, J.D.; Panman, M.R.; Woutersen, S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
3
13
0
Order By: Relevance
“…Interestingly, experiments outside a cavity [22] have shown that vibrational relaxation rates in hydrogenbonded liquids (X H/X D mixture) demonstrate similar sensitive dependence on isotope concentration as we have found inside a cavity in Fig. 4b.…”
Section: Rabi Splitting Dependencesupporting
confidence: 81%
“…Interestingly, experiments outside a cavity [22] have shown that vibrational relaxation rates in hydrogenbonded liquids (X H/X D mixture) demonstrate similar sensitive dependence on isotope concentration as we have found inside a cavity in Fig. 4b.…”
Section: Rabi Splitting Dependencesupporting
confidence: 81%
“…Ethanol-OD in ethanol-OH has an OD-stretch T 1 of 800 fs (Ref. 44) and methanol-OD in methanol-OH of 500 fs, 45 both of which agree well with the 810 fs for the fast component that we observe. To confirm our hypothesis that the fast component is due to Igepal, we also measured the transient response of the OD-stretch vibration in neat Igepal, which reveals a similar fast component of 1.2 ps.…”
Section: Resultssupporting
confidence: 77%
“…The dependence on the isotopic dilution of the fast relaxation time, instead, is still debated. 37,38,42 4 Liquid water…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of hydrogen bonded liquids is usually investigated by labeling the highest frequency vibrational mode, 3 namely: the OH stretching mode. For the sake of comparison with experimental results 37,38 we considered 100% fully deuterated methanol, CH 3 OD and the excitation of the OD stretching mode.…”
Section: Probing the System Relaxationmentioning
confidence: 99%